An Easy-to-Use Method for Assessing Nitrate Contamination Susceptibility in Groundwater. (15th May 2018) - Ducci, Daniela
Abstract : This research presents a methodology for assessing nitrate contamination susceptibility in groundwater using thematic maps, derived mainly from the land use map and from statistical data available at national/regional institutes of statistics (especially demographic and environmental data). The methodology was applied in a large area of southern Italy encompassing 4 alluvial and volcanic groundwater bodies, with high concentrations of NO3 . The Potential Nitrate Contamination is believed to derive from three sources: agricultural, urban, and periurban. The first one is related to the use of fertilizers. For this reason the land use map was reclassified on the basis of the crop requirements in terms of fertilizers to obtain the Agricultural Potential Nitrate Contamination (APNC) map. The urban source considers leakages from the sewage network and, consequently, it depends on the anthropogenic pressure, expressed by the population density, particularly concentrated in the urbanized areas (Urban Potential Nitrate Contamination (UPNC) map). The periurban sources include unsewered areas, especially present in the periurban context, where illegal sewage connections coexist with on-site sewage disposal (cesspools, septic tanks, and pit latrines) (Periurban Potential Nitrate Contamination (PuPNC) map). The Potential Nitrate Contamination (PNC) map is produced by overlaying the APNC, UPNC, and PuPNC maps. The map combination process is straightforward, being an algebraic combination: the output values are the arithmetic average of the input values. The final pollution susceptibility (RISK) map is obtained by combining the PNC map with the groundwater contamination vulnerability (GwVu) map. The methodology, successfully applied in the study area with a relatively good correlation between the nitrate contamination susceptibility map and the nitrate distribution in groundwater, appears to be effective and have a significant potential for being applied worldwide.